2012
DOI: 10.1016/j.ajpath.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Induction of Simple Organogenesis by Mouse Kidney Progenitor Cells in Three-Dimensional Co-Culture

Abstract: Kidney development is regulated by a coordinated reciprocal induction of metanephric mesenchymal (MM) and ureteric bud (UB) cells. Here, established MM and UB progenitor cell lines were recombined in three-dimensional Matrigel implants in SCID mice. Differentiation potential was examined for changes in phenotype, organization, and the presence of specialized proteins using immunofluorescence and bright-field and electron microscopy. Both cell types, when grown alone, did not develop into specialized structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…Additionally, studies on transgenic mice confirmed c-kit expression in hemangioblasts, MM, and also in the epithelial cells of the distal tubules, collecting ducts, ureter and bladder [44]. However, further studies on in vivo lineage tracing of endogenous c-kit + population would bring additional information whether c-kit + cells invade the condensing MM from outside, are a mesenchymal population of cells distinct from the MM cells that will became renal epithelia, or derive from some distinct MM progenitor cell [43,45-47]. …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies on transgenic mice confirmed c-kit expression in hemangioblasts, MM, and also in the epithelial cells of the distal tubules, collecting ducts, ureter and bladder [44]. However, further studies on in vivo lineage tracing of endogenous c-kit + population would bring additional information whether c-kit + cells invade the condensing MM from outside, are a mesenchymal population of cells distinct from the MM cells that will became renal epithelia, or derive from some distinct MM progenitor cell [43,45-47]. …”
Section: Discussionmentioning
confidence: 99%
“…In normal renal development, cells of the ureteric bud (UB), an outgrowth of the Wolffian duct, invade and reciprocally interact with cells of the metanephric mesenchyme (MM) [6][7][8][9][10] to initiate nephron formation. The MM induces UB branching morphogenesis and is, in turn, induced to form neural cell adhesion molecule (NCAM) -positive and paired box gene 2 (Pax-2) -positive caps (four to five cells deep) around the advancing tips of the UB.…”
mentioning
confidence: 99%
“…It has previously been shown that ureteric bud (UB) cell-derived conditioned medium induced metanephric mesenchyme (MM) cell migration. 36 Furthermore, exposure to conditioned media derived from UB and MM cell cultures after stage II (intermediate mesoderm) was effective in inducing the expression of MM and UB markers, respectively, at Stage III (renal lineage). Additionally, it was shown that the conditioned medium from UB cells of embryonic kidneys, when added to pretreated embryonic stem cell cultures, was shown to induce the renal lineages markers Pax2, WT-1, Pod-1, and E-cadherin by gene expression analysis and by FITC-DB (Dolichos biflorus) binding.…”
Section: Discussionmentioning
confidence: 99%